The value of Computed Tomography in the Diagnostic and Prognostic Prediction of Renal Epithelioid Angiomyolipoma - Zhang, Jun; Xu, Xiao-Jian; Chen, Zong-Xin; Zhu, Zheng-Yu; Li, Miao; Hou, Jian-Quan (Urology Journal, 2023)
Purpose: This study aimed to assess the importance of computed tomography (CT) imaging in the diagnostic and prognostic evaluation of renal epithelioid angiomyolipoma (EAML). Materials and Methods: This study comprised 63 patients diagnosed with renal EAML in the First Affiliated Hospital of Soochow University during 2010-2021, who met the inclusion criteria. The clinical, pathological, and therapeutic features were analyzed to determine the optimum diagnostic and therapeutic approaches. Results: Of the 63 participants, 20 were men and 43 women aged 24-74 years (average, 45.5 years). In 35 and 28 participants, the tumor was located on the left and right sides, respectively. All the patients underwent CT scanning. Most of the patients (54/63) with EAMLs demonstrated hyperattenuation, one showed isoattenuation, and eight showed hypoattenuation compared with renal parenchyma on unenhanced CT images. The diameter of each tumor was 2-25 cm (average, 5.6 cm). All the participants underwent surgical treatment. Of these, 53 were followed up for 4-128 months (median, 64 months). Among the followed-up patients, one died of the tumor, one died due to acute severe pancreatitis, and two had an ipsilateral recurrence. Conclusion: EAML is a relatively rare renal angiomyolipoma depleted in fat. A characteristic of hyperattenuation on unenhanced CT images in EAML can help distinguish this tumor from clear cell renal cell carcinoma. Surgical resection is the main treatment. Most EAMLs are benign, and only a few have malignant potential. However, post-surgery recurrence and metastasis may occur, especially in elderly patients, and thus close follow-up is recommended.